2018
DOI: 10.1016/j.jsams.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation status of the TIMP2 and ADAMTS4 genes and patellar tendinopathy

Abstract: To our knowledge, this is the first study to investigate how DNA methylation impacts on the risk of human tendinopathy. Our data indicate that the methylation status of the ADAMTS4 gene is altered in patellar tendinopathy and we speculate on how this change might modify the patellar tendon extra-cellular matrix environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, they did report an overrepresentation in the tendinopathy group of certain inferred pseudohaplotypes from the combination of these polymorphisms, as well as pseudohaplotypes of the collagen XI polymorphisms in combination with COL5A1 rs7174644 (-/AGGG) genotype 30 . Finally, a more recent line of investigation has been epigenetic risk factors for tendinopathy, particularly DNA methylation and its effects on expression levels of genes regulating collagen and other components of the ECM 31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did report an overrepresentation in the tendinopathy group of certain inferred pseudohaplotypes from the combination of these polymorphisms, as well as pseudohaplotypes of the collagen XI polymorphisms in combination with COL5A1 rs7174644 (-/AGGG) genotype 30 . Finally, a more recent line of investigation has been epigenetic risk factors for tendinopathy, particularly DNA methylation and its effects on expression levels of genes regulating collagen and other components of the ECM 31 .…”
mentioning
confidence: 99%
“…Considering the existing literature on the relationship between genetic factors and tendinopathy, this study aims to examine the association of different SNP genotypes with structural abnormalities indicative of elbow tendon pathology, namely COL5A1 rs12722, COL11A1 rs3753841, COL11A1 rs1676486 and COL11A2 rs1799907, selected in order to compare results with previous studies on patellar 24,31 , Achilles 13,25 and elbow tendinopathies 14 .…”
mentioning
confidence: 99%
“…Three studies identified used targeted approaches to identify DE methylated CpGs associated with genes of interest in patellar and the posterior, central and anterior cuff tendons. Two of the studies used diseased and healthy patellar tendon, from healthy Caucasian male patients aged 19–41, to identify changes in the epigenome in relation to tendinopathy 63 , 64 with each paper reporting a specific site; Adamts4 CpG—2995 upstream of promoter 64 and the CpG +61 upstream of MMP11 first exon, 63 these genes are known to translate to tendon specific proteases, involved in the maintenance of proteoglycans and the extracellular matrix. While these studies have shown that controlled analysis of the DNA sequence using a targeted approach revealed some changes in methylation at specific single CpG sites, functional significance remains to be verified, as no parallel gene expression analysis were undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…In turn of the hypermethylation of the MMP11 promotor, the authors speculated that MMP11 substrates would accumulate in the tendon matrix as the amount of the MMP11 enzyme available for catalysis would be limited. The misbalance of the protein composition of the tendon matrix will thereby lead to degenerative progression [29,30]. Altered methylation status of CpG islands upstream of the ADAMTS4 gene, but not the TIMP2 gene, was also associated with human patellar tendinopathy [29,30].…”
Section: Tissue Changes: Histopathological Structural Cellular Epimentioning
confidence: 99%
“…The misbalance of the protein composition of the tendon matrix will thereby lead to degenerative progression [29,30]. Altered methylation status of CpG islands upstream of the ADAMTS4 gene, but not the TIMP2 gene, was also associated with human patellar tendinopathy [29,30]. Review analysis of Vitamin C, a known critical cofactor of collagen synthesis, has also proposed that this vitamin can regulate epigenetic signatures by enhancing the activity of DNA and histone demethylases in the cell nucleus, thus steering a cell reprogramming towards more pluripotent state, which may influence the ECM/collagen homeostasis also in the tendon.…”
Section: Tissue Changes: Histopathological Structural Cellular Epimentioning
confidence: 99%